(untitled) (Research, Society and Development, 2021)
This paper had the objective of making a narrative review through a bibliographical research on the articles developed in the experimental site Amazon Tall Tower Observatory (ATTO). In front of the database proposed by the Max Planck Institute, which has all peer-reviewed publications made within the ATTO experimental site from 2012 to 2021. So in this database, 81 peer-reviewed articles were found, where 12 were classified as a research area Ecological Studies (EE), 15 as Meteorological Conditions and Flows (CMF), 48 as Atmospheric Composition Measurements (MCA) and 6 characterized as Hybrids (H). The journal with the largest publications of this project is Atmospheric Chemistry and Physics, having published 29 articles from 2012 until September 24, 2021. So it can be concluded that during these 9 years of publications, the researches done on the ATTO experimental site were of great importance for understanding the effects of climate change in the Amazon Forest and a growing increase in this research over the years is expected.